2008
DOI: 10.1210/en.2007-1382
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Differentiation of the External Genitalia and the Timing of Puberty in the Presence of an Antiandrogen in Sheep

Abstract: Testicular steroids during midgestation sexually differentiate the steroid feedback mechanisms controlling GnRH secretion in sheep. To date, the actions of the estrogenic metabolites in programming neuroendocrine function have been difficult to study because exogenous estrogens disrupt maternal uterine function. We developed an approach to study the prenatal actions of estrogens by coadministering testosterone (T) and the androgen receptor antagonist flutamide, and tested the hypothesis that prenatal androgens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…The adult reproductive and metabolic phenotype of prenatal testosterone-treated sheep, similar to prenatal testosterone-treated monkeys [3,7], recapitulates the phenotype seen in women with polycystic ovary syndrome (PCOS) [8][9][10]. Parallel studies in sheep with prenatal dihydrotestosterone (DHT; nonaromatizable) [11][12][13] or prenatal exposure to testosterone plus an androgen antagonist (flutamide) [14] have found that some adult reproductive defects may stem from aromatization of testosterone to estrogen. As such, while the adult consequences of exposure to prenatal testosterone excess have been investigated in depth, it remains to be established whether the fetus is exposed to both increased androgens and estrogens following gestational testosterone treatment, and, if so, at what site conversion to estrogen occurs.…”
Section: Introductionmentioning
confidence: 78%
“…The adult reproductive and metabolic phenotype of prenatal testosterone-treated sheep, similar to prenatal testosterone-treated monkeys [3,7], recapitulates the phenotype seen in women with polycystic ovary syndrome (PCOS) [8][9][10]. Parallel studies in sheep with prenatal dihydrotestosterone (DHT; nonaromatizable) [11][12][13] or prenatal exposure to testosterone plus an androgen antagonist (flutamide) [14] have found that some adult reproductive defects may stem from aromatization of testosterone to estrogen. As such, while the adult consequences of exposure to prenatal testosterone excess have been investigated in depth, it remains to be established whether the fetus is exposed to both increased androgens and estrogens following gestational testosterone treatment, and, if so, at what site conversion to estrogen occurs.…”
Section: Introductionmentioning
confidence: 78%
“…In pigs, the AR is considered a candidate gene for reproduction and performance traits (Trakooljul et al 2004). Manipulation of fetal androgen exposure alters the timing of puberty in sheep (Jackson et al 2008). The genes TAF1 and TAF9B encode transcription factors that form the TFIID complex, a regulator of cell cycle and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The defects in steroid negative feedback and augmented pituitary responsiveness to GnRH together contribute to the luteinizing hormone (LH) excess and consequent functional hyperandrogenism seen in prenatal T-treated females (Figure 2). Further studies investigating the effects of prenatal treatment with T, dihydrotestosterone (DHT), a non-aromatizable androgen, or co-administration of the androgen antagonist, flutamide, with T have pointed to disruptions of E 2 negative feedback being programmed by androgenic action of T, with both T and DHT and not T + flutamide reducing sensitivity to E 2 [17, 45, 50]. On the other hand, disruptions in E 2 positive feedback were found in T- but not DHT-treated females suggesting that this defect is likely programmed via estrogenic actions of prenatal T [17, 45].…”
Section: Neuroendocrine Disruptionsmentioning
confidence: 99%